Analisis Kepatuhan Jadwal Kerja dan Istirahat dalam Meningkatkan Disiplin Kerja Karyawan - Sarahono, Herti Trilianti; Rahayu, Enik (Mahesa Research Center, 2025)
This article aims to analyze compliance with work and break schedules in improving employee work discipline. The issue focuses on how the implementation of appropriate work and break schedules can influence employees' discipline levels and productivity within an organization. To approach this issue, references are used from human resource management theories, particularly those related to work discipline and time efficiency. Data were collected through a quantitative research method by distributing questionnaires to employees and conducting interviews with management to gain a deeper understanding of work and break schedule policies. Data analysis was carried out descriptively to illustrate the relationship between schedule compliance and increased work discipline. The study results indicate that employees who adhere to established work and break schedules tend to have higher discipline levels, demonstrate better productivity, and possess a greater sense of responsibility for their tasks. This study concludes that compliance with a structured work and break schedule plays an essential role in creating a more orderly, professional, and efficient work environment. Therefore, continuous supervision and evaluation of work and break schedule policies are necessary to ensure optimal positive impacts on employees and the company as a whole